Screening of accessions from fiber flax collection by productivity and their adaptability to the conditions of the North-West region of Russia - I. A. Kuzemkin; T. A. Rozhmina (Аграрная наука Евро-Северо-Востока)
The article presents the results of evaluation of 19 collection accessions of fiber flax in the conditions of the North-West of Russia (Tver region). The experiments were carried out in 2015-2017 on soddy-podzolic light loamy soil. The most favorable conditions for the formation of high yields of flax fiber were formed in 2017 (Ij = 0.52), for flax seeds ‒ in 2015 (Ij = 0.07). According to the flax fiber yield, such varieties as Tost 3, Atlant (Russia), Evea (France), Alizee, Merylin, (Holland) have been noted, their yield was in the range of 1.65 (Atlant) ... 2.18 (Evea) t/ha, which is 17.0...51.3 % higher than the standard Alfa variety. The variability of this trait in domestic varieties Tost 3 and Atlant is average (CV = 22.58 and 33.31 %, respectively). The varieties of West European breeding Evea, Alizee, Merylin have high variability (CV = 35.02…41.70 %). Varieties Merylin, Evea and Atlant also showed a high yield of flax seeds 0.77...0.82 t/ha with the variability level of 21.31...28.58 %. These genotypes significantly exceeded the average value for this trait – coefficient of adaptability (CA) was 1.10…1.25. According to the results of a comprehensive assessment of fiber flax accessions, including the yield of fiber and seeds, as well as their adaptive properties - stress resistance (Y2 - Y1), genetic flexibility and compensatory ability (Y1 + Y2 / 2), stability (d), the highest indicators were shown by the varieties Tost 3, Atlant and Evea. These genotypes are a valuable source material in fiber flax breeding for adaptability. The expansion of sown areas under these varieties in the conditions of the North-West region of Russia will contribute to solving the problem of the country's raw material supply.